Polysaccharide Based Hybrid Materials Metals and Metal Oxides, Graphene and Carbon Nanotubes - Vilela, Carla (Biobased Polymers,, 2018)
This brief explores polysaccharides, the most abundant family of naturally occurring polymers, and explains how they have gained considerable attention in recent decades as a source of innovative bio-based materials. The authors present a range of material including an extensive array of polysaccharide hybrid nanomaterials with distinct applications. The most recent knowledge regarding polysaccharide-based hybrid nanomaterials with metal and metal oxide nanoparticles (NPs), carbon nanotubes and graphene is presented as well as the main polysaccharides, namely cellulose, chitin and chitosan, starch and their most relevant derivatives. The book features a description of important production methodologies, properties, and applications of these types of hybrids.